Ms. Frizzle's adventures : Imperial China - Cole, Joanna (Scholastic Press, 2005)
Ms. Frizzle and her tour group are transported to China 1000 years in the past, where they learn how rice, tea and silk are grown and harvested, and visit the Emperor in the Forbidden City.